Perceived competence in ice hockey and its associations with relative age, early sport specialization, and players’ position - Huard Pelletier, Vincent; Lemoyne, Jean (Frontiers in Psychology, 2024)
Introduction: Ice hockey is a sport that has gained much attention in recent times, particularly concerning the development of young players. In the domain of youth sport development, one significant factor that must be considered is the perceived competence of players. This variable is closely linked to positive psychological outcomes and sustained practice. However, there is a lack of understanding about how other important developmental factors such as age, early sport specialization, players’ position and relative age affect players' perceived competence. Therefore, the objective of this study is to explore the relationships between these developmental factors, perceived ice hockey competence and a global measure of perceived sport competence. Methods: Data was drawn from 971 players (14.78±1.61 mean age), who completed on-line questionnaires, from which we conducted path analyses involving all variables. Results: Younger players tend to display higher perceived competence scores than older players. Additionally, players who opted to specialize earlier also reported higher perceived competence. Furthermore, forwards and defensemen had differing perceptions of their competence, which was in line with their respective roles on the ice. The study also showed relative age effects, in which players who were born earlier relatively to the selection period tend to perceive themselves more advantageously in three components of perceived competence. Discussion: Based on these findings, several recommendations are proposed for coaches and decision-makers to encourage the positive development of ice hockey players. The study highlights that ice hockey-specific competencies are influenced by various factors, such as early sport specialization, relative age effect, player age, and position.